Sulfur-Containing Radical Anions Formed by Photolysis of Thiosulfate: Quantum-Chemical Analysis - Fedunov R. G. Roman; Pozdnyakov I. P. Ivan; Isaeva E. A. Evgeniya Andreevna; Zherin (Gerin) I. I. Ivan Ignatyevich; Egorov N. B. Nikolai Borisovich (2023, 2023)
Title screen